A distinctive new species of Xyrodromeus Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae) from Madagascar - Gattolliat, Jean-Luc (Zootaxa, 2004)
The genus Xyrodromeus Lugo-Ortiz & McCafferty was established for Afrotropical species of Baetidae (Ephemeroptera) possessing bladelike mandibles. Recently, three new species were described from Madagascar. Xyrodromeus ambiguus n. sp. is established for larvae collected in the North and North-East of Madagascar. It possesses most of the generic features of Xyrodromeus, but differs significantly from all the previously known species by possessing two rows of denticles on the tarsal claws. This species has an intermediate position between Xyrodromeus and Dicentroptilum Wuillot & Gillies. While it may confirm the strong relationship between the two genera, it also opens the question of their validity and could suggest that all these species belong to a single variable and graded genus.